Generalized criteria for evaluating hotspot identification methods. (September 2020) - Guo, Xiaoyu; Wu, Lingtao; Lord, Dominique
Highlights: Three HSID method evaluation tests are generalized and enhanced: HCCT, CSCT, and ARDT. HCCT evaluates a HSID method's reliability in identifying sites with high crash counts. CSCT measures a HSID method's consistency in identifying common hazardous sites. ARDT assesses a HSID method's consistency in measuring the absolute differences in rankings. The generalized tests are capable of evaluating HSID methods over multiple periods, and the results are more consistent. Abstract: Hotspot identification (HSID) is one of the most important components in the highway safety management process. Previous research has found that hazardous sites identified with different methods are not consistent. It is therefore necessary to evaluate the performance of various HSID methods. The existing evaluation criteria are limited to two consecutive periods, and do not consider the temporal instability of crashes. In addition, one existing criterion does not precisely evaluate HSID method under given circumstances. This paper proposed three generalized criteria to evaluate the performance of HSID methods: (1) High Crashes Consistency Test (HCCT) is proposed to evaluate HSID methods in terms of their reliabilities of identifying sites with high crash counts; (2) Common Sites Consistency Test (CSCT) is proposed to gauge HSID methods in consistently identifying a set of common sites as hazardous sites; and, (3) Absolute Rank Differences Test (ARDT) is proposed to measure the consistency of HSID methods in measuring the absolute differences in rankings. Further, three commonly used HSID methods are applied to estimate crashes on Texas rural two-lane roadway segments with eight years of crash data. The performance of these three HSID methods were evaluated to validate the proposed criteria. Comparisons between the existing criteria and the generalized criteria revealed that: (1) the generalized criteria are capable of evaluating different HSID methods over multiple periods; and (2) the generalized criteria are enhanced with a consistent result and with less discrepancy in scores of the best identified HSID method.